A retrospective audit of clinicopathological attributes and treatment outcomes of adolescent and young adult non-Hodgkin lymphomas from a tertiary care center - Sengar, Manju; Akhade, A; Nair, R; Menon, H; Shet, T; Gujral, S; Sridhar, E; Laskar, S; Muckaden, M (Indian Journal of Medical and Paediatric Oncology, 2011)
Background: The uniqueness of adolescent and young adult (AYA) non-Hodgkin lymphomas (NHL) with respect to biology and treatment have largely remained unanswered due to marked heterogeneity in treatment, paucity of prospective, or retrospective studies and poor representation of AYA in clinical trials. This audit attempts to put forward the clinicopathological attributes and treatment outcomes of AYA NHL treated with both pediatric and adult protocols from a single centre in a developing country. Patients and Methods: Hospital records of all consecutive NHL patients registered in lymphoma clinic from January 2007 to May 2010 were reviewed for information on demography, clinical features, histology subtype, staging, treatment regimen, response rates, toxicities, and follow up. Two-year progression-free (PFS) and overall survival (OS) were calculated with Kaplan-Meier method. Results: AYA NHL constituted 4% of all lymphomas. Diffuse large B-cell (DLBL) was the most frequent subtype. Following were the 2-year PFS and OS - DLBL 64%, 76.9%, Burkitt′s lymphoma: 56%, 56%, lymphoblastic lymphoma: 33.2%, 44%. Our results did not show any improvement in outcome of DLBL with the use of Burkitt′s lymphoma like regimen. Conclusions: This study highlights some of the key features of AYA NHL occurring in developing world.
Keywords: Adolescent and young adults; adolescent and young adults malignancies; non-Hodgkin lymphoma